How Important are Human Resources in Supporting Sharia Banking Performance in Indonesia? - Zulfikar, Zulfikar (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
Research by the author is a type of research that combines qualitative andquantitative methods in looking at how influential Human Resources ison the performance of Islamic banking in Indonesia. This study takes datafrom the Financial Services Authority in addition to using data collectionand analysis methods based on the writer’s understanding by looking atthe current issue. Human Resources in Islamic banking needs to be oneof the main points to develop more exceptional Islamic banking and beable to survive and compete with conventional banking. HR is one of theessential factors in supporting the performance of this industry so that itcan be even better in the future by applying the principles of sharia to allsharia banking workers.